Localização de alterações cromatínicas em espermatozoides de touro e sua relação com a marcação imunocitoquimica de protamina - Souza, Elisson Terêncio (2014)
Changes in the chromatin of sperm have been linked to subfertility in several species of mammals. One of the factors that leads to these changes is protamine deficiency. In this study we analyzed the location of changes of chromatin in the sperm of bulls and the relationship with the markup of protamine immunocytochemistry. Semen samples of fertile and subfertile bulls were examined through computational analysis of images of smears stained with toluidine blue (TB), DAPI and marked with protamine 1 (PR1) antibody. For the evaluation TB blades were used in two separate analyses: a conventional, where we obtained the value of decompression percentage (DESC%) and average chromatin heterogeneity (HET) of sperm, and an alternative, which labels changes according to the location of the change in the head of the sperm and percentage of sperm with each type of change in the samples. In both was compared samples from fertile and subfertile bulls. Conventional analysis showed a significant increase (p = 0.01) both DESC% and HET in subfertile samples. On the other hand, alternative analysis showed an increase in subfertile samples of changes in basal half (AMB) p = 0.05 and totally changed heads (CTA) p = 0.04. This alternative computational analysis was also applied to staining with DAPI, where the subfertile samples showed an increase in base alterations (AB) p = 0.02. The dispersed changes (AD) were higher with p = 0.02 in the fertile samples. On labeling with anti-PR1, changes in the base (AB) were higher in subfertile samples with p = 0.01. With these results we conclude that, with the alternative technique was possible to propose a classification of changes in staining and immunolabelling, but this technique showed a low efficiency to distinguish fertile from subfertile bulls. DAPI staining assessed in confocal microscopy is presented as a possible alternative for staining with AT. The conventional technique with AT showed the best result for differentiation between fertile and subfertile groups. PR1 Immunostaining showed that this protein is distributed throughout the bull sperm head, and that chromatin alterations in these cells have no relation with the amount of PR1.